Theoretical kinetic study of the reactions between pyridyl radicals and O2 - Konnov, Alexander A.; Savchenkova, Anna S.; Xie, Jibiao; Matveev, Sergey S.; Matveev, Sergey G.; Mebel, Alexander M. (Fuel, 2026)
Reactions of the primary pyridine radicals, ortho-, meta-, and para-pyridyls with oxygen control the overall rate of pyridine oxidation. In the present work, the potential energy surfaces of o-, m-, and p-pyridyls + O2 previously developed by the authors have been employed for a systematic theoretical kinetic study of the rate constants of these reactions. The geometries of reactants, products, intermediates, and transition states of the reactions of pyridyl radicals with O2 were optimized at the level of density functional theory using the ωB97XD functional with the 6-311G** basis set. The temperature- and pressure-dependent rate constants of 31 reactions were evaluated within the framework of the Rice-Ramsperger-Kassel-Marcus (RRKM) theory combined with the Master Equation approach (RRKM–ME) in the temperature range from 300 to 3000 K, covering pressures from 0.01 to 100 atm. For several reactions previously investigated in the literature, good agreement was demonstrated, indicating consistency and correctness of the present theoretical calculations. Moreover, thermodynamic data for all important reactants, products, and intermediates have been revisited and calculated at the G4 theoretical level. The calculated rate constants and thermodynamic data provide a backbone for the development of detailed kinetic models for pyridine combustion.
Keywords: Oxidation; Pyridine; Pyridyl radicals; Rate constant; Thermodynamic data